Sudanese totalitarianism: violent jihad as a state policy [version 2; peer review: 1 approved, 3 approved with reservations] - Karolina Zielińska (Stosunki Międzynarodowe)
The case of Sudanese violent jihadism is a specific one, starting from 1881–1899 Mahdist’s uprising. Since the 1956 independence, the history of Sudan has been marked by civil wars taking place in various parts of its huge territory; violence under the outwardly jihadist banner culminated in the 1990s. The Islamic state used violent jihad, by the army and by militias, as a way to impose unitary rule (state-building) and shari’a law upon a significantly diversified population. Violent Jihad was thus called for three purposes: to mobilise resources for fight with non-Muslim southern Sudanese; to consolidate the Muslim north internally in the context of the struggle of the totalitarian regime against opposition and struggles within the regime itself; and to define the international role of Sudan as a supporter of radical Islamic movements. The case of Sudan is thus one in which violent jihad was part of the state ideology and an instrument of policy.